Multistakeholder Dialogue Facilitation - Minh, Thai Thi; Ofosu, Abena; Melaku, Dagmawi (International Water Management Institute, 2023)
Creating and facilitating Multi-stakeholder Dialogues help bring different perspectives, specific experiences, and shared interests for collaborations and interactive learning.